(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
India is a democratic nation where political parties play an important role in this democracy. In India, all the political leaders are selected by the common people through the process of general elections. The winning leaders represent their corresponding constituencies. Prime Minister is the chief leader of all the leaders and has the authority to take effective actions in order to make further developments in the country. Indian democracy is by the people and for the people. The common people have the right to choose their leaders. In India, every person having an age of equal or more than that of 18 has the right of voting. The current paper highlights the role of political parties in Indian democracy.